Glycan-Foraging Systems Reveal the Adaptation of Capnocytophaga canimorsus to the Dog Mouth - Francesco Renzi (American Society for Microbiology, 2015)
ABSTRACT Capnocytophaga canimorsus is known to form two kinds of cells on blood agar plates (coccoid and bacillary), evoking phase variation. When grown in coculture with animal cells these bacteria appeared only as bacilli, but in the presence of vancomycin they were round, indicating that coccoid shapes likely result from weakening of the peptidoglycan layer. Polysaccharide utilization locus 5 (PUL5) and sialidase mutant bacteria, unable to retrieve glycans from glycoproteins, grew less than wild-type bacteria and also appeared polymorphic unless GlcNAc was added, suggesting that C. canimorsus is unable to synthesize GlcNAc, an essential component of peptidoglycan. Accordingly, a genome analysis was conducted and revealed that C. canimorsus strain 5 lacks the GlmM and GlmU enzymes, which convert glucosamine into GlcNAc. Expression of the Escherichia coli GlmM together with the acetyltransferase domain of GlmU allowed PUL5 mutant bacteria to grow normally, indicating that C. canimorsus is a natural auxotroph that relies on GlcNAc harvested from the host N-glycoproteins for peptidoglycan synthesis. Mucin, a heavily O-glycosylated protein abundant in saliva, also rescued growth and the shape of PUL5 mutant bacteria. Utilization of mucin was found to depend on Muc, a Sus-like system encoded by PUL9. Contrary to all known PUL-encoded systems, Muc cleaves peptide bonds of mucin rather than glycosidic linkages. Thus, C. canimorsus has adapted to build its peptidoglycan from the glycan-rich dog's mouth glycoproteins. IMPORTANCE Capnocytophaga canimorsus is a bacterium that lives as a commensal in the dog mouth and causes severe infections in humans. In vitro, it forms two kinds of cells (coccoid and bacillary), evoking phase variation. Here, we show that cell rounding likely results from weakening of the peptidoglycan layer due to a shortage of N-acetylglucosamine (GlcNAc). C. canimorsus cannot synthesize GlcNAc because of the lack of key enzymes. In its niche, the dog mouth, C. canimorsus retrieves GlcNAc by foraging glycans from salivary mucin and N-linked glycoproteins through two different apparatuses, Muc and Gpd, both of which are related to the Bacteroides starch utilization system. The Muc system is peculiar in the sense that the enzyme of the complex is a protease and not a glycosylhydrolase, as it cleaves peptide bonds in order to capture glycan chains. This study provides a molecular genetic demonstration for the complex adaptation of C. canimorsus to its ecological niche, the oral cavity of dogs.